Quantifying damages for antitrust offences, quo vadimus? - Martín Martín, Gustavo Andrés (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The mechanism of judicial assessment is playing an important role in the determination of injury by the Spanish courts in the truck cartel case. Once established the general framework of the criteria used by the Spanish courts in these cartel cases, the question arises as how this mechanism is being applied by Courts. This study shows that the judicial assessment of damages operates on two different levels with important substantive and procedural consequences.
Keywords: competition; damages; judicial estimation